La ruptura epistemológica, de Bachelard a Balibar y Pêcheux - Karczmarczyk, Pedro Diego (2013)
In the present paper we analyze a tradition of reflections on scientific knowledge which distinguish it because of its "discontinuity" with common sense or ordinary knowledge. The beginning of this tradition can be traced back to Gaston Bachelard and his peculiar study of the epistemological acts which allows a scientific field to break with its past. The study of these acts helps to overcome what Bachelard considers is the empiricist myth of continuity of knowledge. Bachelard’s views were retaken by Althusser and further developed by his students Balibar and Pêcheux. We will try to show the common commitment with discontinuity is an homogeneous view. Consequently we will try to show differences in the way of understanding discontinuity. The revision of his own positions made by Althusser in his “Self-criticism” is a special standpoint in order to consider the alternatives that his disciples developed on different grounds.